Dab1 stabilizes its interaction with Cin85 by suppressing Cin85 phosphorylation at serine 587 - Bior, Bior K. (2012)
Crk and CrkL adaptors play essential neuronal positioning roles downstream of Reelininduced Dab1 tyrosine phosphorylation. Recently we identified Cin85 to be a CrkL-SH3 binding partner from embryonic murine brain while others found Cin85 binds directly to Dab1. Here using mass spectrometry, biochemical and mutational analyses we show that Dab1 suppresses Cin85 phosphorylation at Ser587. Furthermore a Cin85 Ser587 phosphomimetic disrupts the Dab1-Cin85 complex without affecting the Cin85-CapZ complex. These data provide an early glimpse into how Cin85 phosphorylation might alter the composition of its scaffolding partners to regulate its diverse roles including vesicular trafficking, receptor endocytosis and actin remodeling.